Analyze of Tourism Potential Tiku Beach Agam Regency as a Marine Tourism Destination - Husna, Rifdatul; Sari, Windy Della; Zengga, Zengga (Politeknik Negeri Bengkalis, 2024)
This research aims to identify and map the tourism potential of Tiku Beach, Tanjung Mutiara District, AgamRegency, based on the theory of 4A Tourist Destination Components, namely attraction, accessibility, amenities andancillary service. Tiku Beach has an attraction for marine tourism, namely in the form of views of the beach and waterswith natural coral reefs. The coastal view is unique, still beautiful, white sand with a wide coastline and a fairly slopingcontour facing directly to the Indian Ocean. The potential that exists at Tiku Beach can be developed into a superior marinetourism destination. This research uses a qualitative descriptive approach. Data was collected using observation, interviewsand literature study methods. Data analysis in this research is inductive, carried out through a process of data reduction,data verification and data presentation. The data that has been collected is then processed and analyzed using descriptivetechniques. The research results show that Tiku Beach has the potential to be pioneered and developed into a marine tourismdestination. There is still a need to improve each component of the 4A tourist destinations in this area, especially theamenities and anciallary service components. Coordination and synergy of all elements of the tourism pentahelix are neededto accelerate tourism activities at Tiku Beach, Tanjung Mutiara District, Agam Regency.